Why Mudzakarah Still Matters: A Classical Learning Practice for Strengthening Arabic Grammar Understanding - Kasmiati, Kasmiati; Andrian, Riko; Syansi, Aqiilah Hana; Gama, M. Adri; Putri, Safira (Borneo Journal of Language and Education, 2026)
Mudzakarah is a traditional Islamic learning method still used today. It helps students understand what they learned in class. Although well-known, there are few studies on its use in learning Arabic at Islamic schools. This study looks at how mudzakarah is used and its impact on fifth-grade girls learning Arabic at Pondok Pesantren Dar Al-Nahda Thawalib Bangkinang. The study uses a qualitative approach and descriptive method. Data were collected through observation, interviews, and document analysis. The subjects were fifth-grade girls in the diniyah education program. The results show that mudzakarah involves structured group discussions, Q&A sessions, and repeating learned material. This method helps reinforce learning and encourages active participation. The study found that mudzakarah improves understanding of Arabic grammar rules, especially in reading and understanding texts. It also boosts confidence, motivation, and cooperation among students. Factors that help mudzakarah work well include a supportive school environment and motivated students. Challenges include differences in student abilities and limited time. Overall, mudzakarah plays a key role in improving understanding of Arabic grammar and supports effective language learning in Islamic schools.